Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pada Dinas Koperasi Usaha Kecil Menengah Perdagangan Dan Perindustrian Kota Bogor - Dhelvia Devitha Shalihah; Purwatiningsih Purwatiningsih; Elmira Siska (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The development of the era of globalization is increasingly developing and making human work easier in research. This research aims to find out how much influence discipline and the work environment have on employee performance at the Bogor City MSME Service. The research method is a quantitative approach using nonprobability sampling data collection techniques. The number of samples using the Slovin formula was 56 respondents. Primary data was collected using questionnaires in Likert scale units. Data processing uses SPSS 26 software for instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of this research were proven in the partial test on the discipline variable (X1) of 0.000 < 0.05 and the calculated t value of 5.352 > t table value of 2.005 that H0 was rejected and Ha was accepted and on the environmental variable (X2) of 0.005 < 0.05 and the calculated t value of 0.661 < t table 2.010 so that H2 is accepted, meaning that the environment has no statistically significant effect on performance (Y). Then, through simultaneous testing of the two variables at a calculated F value of 24,271 > F table 3.17 and a significance of 0.000 < 0.05, it is concluded that H0 is rejected and H1 accepted, which means that both discipline variables (X1) and environmental variables (X2) simultaneously influence performance (Y).